FUNCTIONAL EMPOWERMENT FACTORS AND THEIR IMPACT ON ENHANCING THE CORE CAPABILITIES OF THE ORGANIZATION / A FIELD STUDY AT AL-MUSTANSIRIYA CENTER FOR ARAB AND INTERNATIONAL STUDIES / AL-MUSTANSIRIYA UNIVERSITY - Lecturer Mustafa Saadi Talib (American Journals, 2023)
The aim of the research is to identify the functional empowerment factors and their impact on enhancing the core capabilities within the research community. In this research, the descriptive analytical method was used. The research community consists of a group of teachers and employees of the Al-Mustansiriya Center for Arab and International Studies at Al-Mustansiriya University, who number (38) affiliates. The questionnaire forms were distributed to all members of the sample. The research questionnaire was designed based on previous studies related to the subject of the research. Statistical means the researcher concluded that there is an effect of applying the functional empowerment factors on enhancing the core capabilities in the organization in the field of research.
Keywords: Functional empowerment factors, Core capabilities